Multilingualism as an advantage or an obstacle to the early acquisition of Croatian - Aladrovic Slovacek, Katarina; Rimac Jurinovic, Maša (Journal of Child Language Acquisition and Development - JCLAD, 2021)
One of the goals of the European Union's language policy is multilingualism and multiculturality which contribute to creating a multilingual community.Research that was conducted in Croatian primary schools indicates that learning a foreign language positively affects the mother tongue acquisition, i. e. that parallel language codes are not an obstacle but rather an advantage in the process of acquiring standard Croatian language. Various factors influence children's early stages of language acquisition, like e. g. media a child is exposed to (cartoons in different languages, language of advertisements and of computer games), the environment in which a child is raised and most of all, speech models in the family (parents) and kindergarten (kindergarten teachers), the acquisition of, i. e. learning a second language to which a child is exposed being an additional factor of influence. It is, therefore, the aim of this paper, to examine the interference of parallel language codes of both related languages and those that are not related, but are dominant in a child's environment, with the process of Croatian language acquisition at the kindergarten and preschool age. 15 kindergarten and preschool children (aged 5 and 6) participated in the research and were examined by longitudinal process of monitoring and by short linguistic questionnaire designed for the purpose of the research with the topics of everyday life, colours and animals and a number of pictures were used to prompt children to tell a story orally. It was expected that there would be interference between foreign languages and the process of Croatian language early acquisition and a more significant influence of related Slavic languages and English as a linguae francae. Moreover, it was expected that the interference would not be a difficulty but rather an advantage for acquiring the mother tongue (Croatian).